Employee to entrepreneur : how to ditch the day job and start your own business - Garden, Chris (Pearson, 2013)
Stop dreamingand startyour own business Employee to Entrepreneur shows you how to seamlessly move from employed to self-employed, how to effectively harness, utilise and exploit the skills and expertise you've already gained in your corporate emploment and use them all to help you start your own businessandmake the exciting movefrom employee toentrepreneur. Youcan turn a career brick wall into an exciting opportunity and start your own business.This bookdispels all the myths, dissolves all the obstacles and takes you on a business startup journey that will help you to assess all.